Dor dentária e fatores associados em crianças menores de cinco anos de Goiânia - Lemes, Marília Galvão Chaves (2013)
Dental pain in childhood is a major oral health problem because it may impact the daily activities of children and their families. Although there is a growing number of studies on this issue, those carried out in children under five years old are scarce. The aim of this study was to determine the prevalence of dental pain and associated factors in children under five years old in Goiânia-GO, Brazil. A cross-sectional, population-based household study was carried out, using data of the project "Nutritional profile of children under five years old in the city of Goiania", of the School of Nutrition (FANUT)/UFG. The sample consisted of 385 children aged two to four years. Data were collected through interviews with parents or guardians and anthropometric measures. The variables analyzed were: dental pain some time in their lives (yes/no) and demographic, socioeconomic and health-related factors. For data analysis we used descriptive statistics, bivariate and logistic regression, considering the sample weights. The prevalence of dental pain was 9.9% (CI=7.4-13.1). Children whose mothers had low education were 2.73 (p=0.034) more likely to have tooth pain that children whose mothers had more than 8 years of schooling. Children who regularly consumed artificial juice powder containing sugar were 2.13 (p=0.018) more likely to have dental pain. It was concluded that the prevalence of dental pain was considerable and associated with the level of education of the parents and the children’s industrialized juices consumption. The implementation of strategies for improving living conditions and promoting healthy eating have the potential to reduce oral health problems and impact on quality of life due to dental pain.